695-28%=500.40
695-500.4=194.60 savings. ☺☺☺☺
Answer:6
Step-by-step explanation:
from Pythagoras principle we get
x=√(10^2-8^2)
x=√(10x10-8x8)
x=√(100-64)
x=√(36)
x=6
Answer:
7 + 6
5 + 11
Step-by-step explanation:
the lengths of the two shorter sides of a triangle must add up to more than the length of the third side.
3 + 4 = 7 ≤ 8 no
7 + 6 = 13 > 12 yes
5 + 11 = 16 > 13 yes
4 + 6 = 10 ≤ 12 no
4 + 6 = 10 ≤ 10 no
Answer:
4260
Step-by-step explanation:
3z-4=6z-17
-3z-4=-17 (subtracted the 6z from both sides)
-3z=-13 (added the 4 to both sides)
z=
![\frac{-13}{-3z}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-13%7D%7B-3z%7D%20)
(divided both sides by -3z)
z=